Key Aspects of the Epidemiology of Aujeszky’s Disease – Suid herpesvirus 1 Infection in Swine and Cattle: A Thorough Review - Bitsch, Viggo (Contemporary Research and Perspectives in Biological Science Vol. 4, 2024)
Respiratory airborne and genital infections have occurred worldwide in swine and cattle and there is strong evidence that vaginal infection of cattle was regularly sexually transmitted from sows by man. Aujeszky's disease – infection with Suid herpesvirus 1 (SuHV1) – is an infection of pigs, which can infect several other animal species, regularly with a fatal outcome. It has been found worldwide but is now eradicated in several countries. Denmark is the country, where Aujeszky's disease has been studied most intensively, and the results from investigations of cattle have been of greatest importance for understanding the epidemiology of the infection in swine. Denmark was the first country to initiate and complete eradication. In this review, important epidemiological features are recapitulated at the end of each section or subsection. In cattle, the infection will most often give rise to an intense pruritus of a skin area, preferably on the head, chest, or hindquarters. Anterior localization of pruritus, on the head or chest, was found to be associated with a respiratory infection, while posterior pruritus was linked up with a vaginal infection. Pruritus must be considered a phantom sensation caused by stimulation or damage of the central nervous system including sensory ganglia. Respiratory infection of cattle is a dead-end infection and the source of infection is pigs infected by the respiratory route. Cattle at risk need not necessarily be placed near the infected pigs, as the virus in animals is determined by ventilators over distances of 10-20 meters, even from pigs in a neighboring room. Strong evidence was established of the condition that vaginal infection in cattle had regularly been sexually transmitted by men. In swine, the infection was considered to be exclusively respiratory for decades, but naturally occurring genital infection was demonstrated in 1981. In herds with outbreaks in cattle characterized by pruritus on the hindquarters (vaginal infection), respiratory infection of pigs was never observed but a sow had characteristically been served by a foreign boar approx. one week earlier. In some such cases investigated, genital infection was confirmed in sows, which clearly associated cases in cattle with a posterior localization of pruritus to a concurrent genital infection of swine. Respiratory infection of pigs was demonstrated late in the history of the disease. The observed aggravation of the disease situation in pigs in Denmark clearly illustrated that SuHV1 can change in degree of pathogenicity over time. The changes occurred in two steps. In the early 1960s, respiratory strains developed, which were spread rapidly between herds due to animal contacts, mainly by trade, and later in the 1970s strains developed, which had an even higher degree of pathogenicity for cattle and swine. These new strains were found syncytial in contrast to earlier isolates from traditional outbreaks. The new respiratory syncytial strains had not been introduced from abroad as restriction fragment pattern analyses of virus DNA documented that they possessed special Danish characteristics. The decisive spread of the respiratory infection among swine in a ventilated animal house was found to be by air currents over many meters determined by the ventilation system and not by close animal-to-animal contacts. During an acute outbreak in a swine herd, considerable amounts of virus would be blown out into the surroundings by ventilators, exposing other herds to the risk of infection. Early observations led to the conclusion that airborne spread between swine herds might occur over several kilometers and after eradication of the indigenous infection, new infections were introduced from abroad, which demonstrated that airborne spread of the virus between herds might take place over even 10 to 30 kilometers. Syncytial strains of SuHV1 have shown to possess a pronounced tendency to airborne transmission among swine herds, which implies that if a syncytial strain is first introduced into an area, it is likely to become the prevailing type in that area within a relatively short time. It is a special conclusion from the epidemiological analyses that the SuHV1 infection, before the development of the respiratory infection, had been maintained in the first part of the 20th century in many countries as an unnoticed porcine genital infection.